The hypercoagulable state in COVID-19: Incidence, pathophysiology, and management. Issue 194 (October 2020) - Abou-Ismail, Mouhamed Yazan; Diamond, Akiva; Kapoor, Sargam; Arafah, Yasmin; Nayak, Lalitha
Abstract: The 2019 coronavirus disease (COVID-19) presents with a large variety of clinical manifestations ranging from asymptomatic carrier state to severe respiratory distress, multiple organ dysfunction and death. While it was initially considered primarily a respiratory illness, rapidly accumulating data suggests that COVID-19 results in a unique, profoundly prothrombotic milieu leading to both arterial and venous thrombosis. Consistently, elevated D-dimer level has emerged as an independent risk factor for poor outcomes, including death. Several other laboratory markers and blood counts have also been associated with poor prognosis, possibly due to their connection to thrombosis. At present, the pathophysiology underlying the hypercoagulable state is poorly understood. However, a growing body of data suggests that the initial events occur in the lung. A severe inflammatory response, originating in the alveoli, triggers a dysfunctional cascade of inflammatory thrombosis in the pulmonary vasculature, leading to a state of local coagulopathy. This is followed, in patients with more severe disease, by a generalized hypercoagulable state that results in macro- and microvascular thrombosis. Of concern, is the observation that anticoagulation may be inadequate in many circumstances, highlighting the need for alternative or additional therapies. Numerous ongoing studies investigating the pathophysiology of the COVID-19 associated coagulopathy may provide mechanistic insights that can direct appropriate interventional strategies. Highlights: COVID-19 generates a significantly increased risk for thrombosis Pulmonary inflammation and localized vasculopathy are central to the hypercoagulable state Immune dysregulation is notable in severe illness Rising D-dimer levels correlate with worse outcomes Anticoagulant guidelines are rapidly evolving as we gather further insights